Calcifying Spindle Cell Soft Tissue Tumor With SOX10::PLAG1 Fusion: A Case Report of a Morphologically Distinctive and Potentially Novel Soft Tissue Tumor - Kosemehmetoglu, Kemal; Mosaieby, Elaheh; Šteiner, Petr; Vaněček, Tomáš; Baranovska-Andrigo, Vira; Michal, Michael (Genes, chromosomes & cancer, 2024)
The widespread use of advanced molecular techniques has led to the identification of several tumor types with PLAG1 gene fusions some of which also affect the skin and soft tissues. Herein, we present a 38-year-old female with a subcutaneous tumor affecting her forearm, which does not seem to fit into any currently recognized entity. It was a well-circumscribed tumor measuring 6 × 4,5 × 4 cm. It had a thick capsule composed of bland spindle cells forming palisades and Verocay body-like structures within a myxocollagenous background. Scattered calcifications were dispersed throughout the lesion. No cytological atypia, mitotic activity, or necrosis were present. Targeted NGS revealed a SOX10::PLAG1 fusion and fluorescent in situ hybridization confirmed the presence of PLAG1 gene rearrangement. The neoplastic cells showed a diffuse immunohistochemical expression of S100, SOX10, and PLAG1, as well as patchy desmin and CD34 positivity. The methylation profile of this tumor did not match any other entity covered by the DKFZ sarcoma classifier and apart from the gain of chromosome 12, the copy number profile was normal. The tumor was completely excised, and the patient has been free of disease for 4 years since the excision. While more cases are needed to confirm this tumor as a distinct entity, we propose a provisional name "SOX10::PLAG1-rearranged calcifying spindle cell tumor."
Keywords: soft tissue tumor; SOXE Transcription Factors; DNA-Binding Proteins; fúzní onkogenní proteiny; Sarcoma; Oncogene Proteins, Fusion; lidé; transkripční faktory SOXE; Calcinosis; Adult; nádory měkkých tkání; fusion‐positive mesenchymal tumor; kalcinóza; ženské pohlaví; Humans; sarkom; Soft Tissue Neoplasms; DNA vazebné proteiny; dospělí; Female; PLAG1 gene rearrangement